Recidivism in Switzerland: the influence of custodial sanctions (Swiss Medical Weekly, 2021)
AIMS OF THE STUDYAlthough many studies have investigated the influence of personal characteristics on recidivism, knowledge about the impact of correctional policies remains limited. The present study adds to this debate by investigating the effect of the dualistic system of custodial sanctions in Switzerland over time. Specifically, we: (1) tested the influence that different types of custodial sanctions – sentences (offering regular prison treatment) and measures (offering crime-related rehabilitation programmes) – have on reconviction rates; and (2) forecasted future reconviction rates to estimate their value in the year 2020.METHODSNational level data from the Swiss Federal Statistical Office were collected, including 3-year reconviction rates after release from custody and the number of persons serving custodial sentences and measures. A time series framework was used for the analyses, which included data available from 1988 to 2013 (n = 26 years).RESULTSThe number of persons serving custodial sentences had no effect on recidivism (p = 0.582); however, a higher number of persons serving custodial measures was significantly associated with a decrease in recidivism (p = 0.003). For the year 2020, a reconviction rate of 28% (range 23–33%) was predicted.CONCLUSIONSCustodial measures seem to be associated with a reduction in recidivism. However, owing to the indeterminate time associated with some custodial measures, often at the cost of the prisoners’ rights and the criminal justice system, future studies are needed to determine the optimal serving time for custodial measures.